Measurement of neutral and charged current cross-sections in positron-proton collisions at large momentum transfer - Adloff, C; Andreev, V; Andrieu, B; Arkadov, V; Astvatsatourov, A; Ayyaz, I; Babaev, A; Bahr, J; Baranov, P; Barrelet, E; Bartel, W; Bassler, U; et al. (2000)
The inclusive single and double differential cross-sections for neutral and charged current processes with four-momentum transfer squared Q2 between 150 and 30 000 GeV2 and with Bjorken cursive Greek chi between 0.0032 and 0.65 are measured in e+p collisions. The data were taken with the H1 detector at HERA between 1994 and 1997, and they correspond to an integrated luminosity of 35.6pb-1. The Q2 evolution of the parton densities of the proton is tested, yielding no significant deviation from the prediction of perturbative QCD. The proton structure function F2(cursive Greek chi, Q2) is determined. An extraction of the u and d quark distributions at high cursive Greek chi is presented. At high Q2 electroweak effects of the heavy bosons Z° and W are observed and found to be consistent with Standard Model expectation.